2013
DOI: 10.1097/brs.0b013e3182a40838
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Blood Perfusion in Spinal Metastases With Dynamic Contrast-Enhanced Magnetic Resonance Imaging

Abstract: Study Design.This was a retrospective study focusing on dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) to assess treatment response in patients with spinal metastases.Objective.To demonstrate DCE-MRI changes before and after radiation treatment and correlating with other imaging and clinical findings.Summary of Background Data.Currently, conventional imaging is limited in evaluating early treatment success or failure, which impacts patient care.Methods.Consecutive patients with known spinal met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 19 publications
2
78
0
Order By: Relevance
“…The greater vascularity of RCC, when compared with PC, does not imply that RCC must be more permeable than PC. Based on previous a study, 22 post-treatment V p goes down, but K trans does not change or changes to a lesser extent, which may not be significant. Leakage does not mean high vascularity.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The greater vascularity of RCC, when compared with PC, does not imply that RCC must be more permeable than PC. Based on previous a study, 22 post-treatment V p goes down, but K trans does not change or changes to a lesser extent, which may not be significant. Leakage does not mean high vascularity.…”
Section: Discussionmentioning
confidence: 83%
“…1821 Furthermore, perfusion imaging has been shown to be adept in monitoring the response to radiotherapy of tumors in spinal bone metastases. 22 A recent study has shown that the semi-quantitative metrics extracted from DCE-MRI can differentiate between hypervascular and hypovascular metastatic lesions of the spine. 18 Our aim in this study was to evaluate spinal metastases from RCC and PC using the T1 DCE-MRI perfusion technique and to assess the sensitivity and specificity of perfusion parameters obtained by both quantitative (derived from pharmacokinetic modeling) and semi-quantitative methods, which would allow for noninvasive discrimination between hypovascular and hypervascular spinal metastases.…”
Section: Introductionmentioning
confidence: 99%
“…These quantitative parameters have demonstrated their value in detecting the differences in microvascular environment among metastatic lesions before and after treatment 9 , benign and pathological fractures 10 , and hypovascular and hypervascular lesions. 11,12 Vertebral metastases demonstrate very different histological patterns depending on the primary tumor.…”
Section: Introductionmentioning
confidence: 99%
“…DCE-MRI involves assessing changes in signal intensity over time: before and after contrast injection (12). Previous studies have shown that DCE-MRI is useful for monitoring response to therapy in spinal bone metastases (13), and for discriminating between the hypo- and hyper- vascular spinal lesions of prostate carcinoma and renal cell carcinoma, respectively (14). More recently, DCE-MRI has shown clinical utility in chordoma diagnosis, effectively discriminating between chordoma and giant cell tumors of the axial skeleton (15).…”
Section: Introductionmentioning
confidence: 99%